2015
DOI: 10.1111/jfr3.12198
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to estimate wave‐induced coastal flooding hazard maps in Spain

Abstract: The purpose of the European Flooding Directive (2007/60/CE) is to establish a European framework for the assessment and management of flood risks. The aim is to reduce the adverse flooding consequences on a wide range of topics such as human health, environmental and cultural heritage, and economic activity. In Spain, coastal zone flood hazard and risk maps are managed by the Environment Spanish Ministry (MAGRAMA, Dirección General para la Sostenibilidad de la Costa y el Mar). These maps are designed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The significant total swash S tot and the significant IG swash S IG are estimated from the swash energy spectra E RU ( f ) as SIG=40fpfalse/2ERUfalse(ffalse)normaldf, Stot=40ERUfalse(ffalse)normaldf. A significant dependence of S IG (equation ) and S tot (equation ) on the parameter βHs0L0 is observed (squared correlation coefficients r 2 are, respectively, 0.70 and 0.75); see Figures a and b. The best linear fits forced to pass through the origin are SIG=2.03βHs0L0, Stot=2.11βHs0L0. This dependence implies that the vertical scaling of swash is proportional to the Iribarren number as first suggested by Hunt, (; see also equation (3) of Tomas et al, ) and then confirmed by several studies (Cohn & Ruggiero, ; Holman & Sallenger, ; Ruggiero et al, ; Stockdon et al, ). Moreover, the dependence of S IG on βHs0L0 is higher for broad‐banded runs with γ =1 ( r 2 =0.81) with respect to more narrow‐banded runs (e.g., r 2 =0.59 for runs with γ =13).…”
Section: Resultsmentioning
confidence: 99%
“…The significant total swash S tot and the significant IG swash S IG are estimated from the swash energy spectra E RU ( f ) as SIG=40fpfalse/2ERUfalse(ffalse)normaldf, Stot=40ERUfalse(ffalse)normaldf. A significant dependence of S IG (equation ) and S tot (equation ) on the parameter βHs0L0 is observed (squared correlation coefficients r 2 are, respectively, 0.70 and 0.75); see Figures a and b. The best linear fits forced to pass through the origin are SIG=2.03βHs0L0, Stot=2.11βHs0L0. This dependence implies that the vertical scaling of swash is proportional to the Iribarren number as first suggested by Hunt, (; see also equation (3) of Tomas et al, ) and then confirmed by several studies (Cohn & Ruggiero, ; Holman & Sallenger, ; Ruggiero et al, ; Stockdon et al, ). Moreover, the dependence of S IG on βHs0L0 is higher for broad‐banded runs with γ =1 ( r 2 =0.81) with respect to more narrow‐banded runs (e.g., r 2 =0.59 for runs with γ =13).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning storm dynamics in the Gulf of Lion, focusing, respectively, on surges and waves, Ullmann et al (2008) showed that marine storms do not last longer than 3 days. We therefore decided to select the maximum H s values per 3-day block, with a minimum of 1.5 days between peaks to make sure of their independence.…”
Section: Data Preparationmentioning
confidence: 99%
“…It can also be integrated into a static flood mapping approach (Gallien et al 2014;Didier et al 2015), where the flood elevation is assumed to propagate toward the coast and overland until it reaches a homogeneous and equivalent contour elevation (Vitousek et al 2009;Patrick et al 2015). Wave runup can be calculated at different points along the coast to give a TWL at each cross-shore profile where the slope has been calculated (Tomás et al 2015). On platform-beaches however, the morphodynamic context is different to sandy beaches.…”
Section: Introductionmentioning
confidence: 99%